Advances in pharmacotherapy for the prophylactic treatment of resistant and refractory migraine. (3rd July 2022) - Fitzek, Mira; Raffaelli, Bianca; Reuter, Uwe
ABSTRACT: Introduction: Refractory migraine is associated with low quality of life and great socioeconomic burden. Despite high need for effective, tolerable preventive therapies, there has been little research on potential therapeutic options. Monoclonal antibodies (mAbs) against Calcitonin Gene-Related Peptide (CGRP) are the first preventive therapeutic approach for migraine based on the underlying pathophysiology. Areas covered: Following a brief introduction into the term 'refractory migraine, ' the authors reviewavailable treatment options, focusing on current phase III trials of substances acting on the CGRP pathway. Expert opinion: No uniform definition for refractory migraine is available. The vast majority of proposals recommend treatment failure of 2–4 drug classes as a key diagnostic criterion. Phase III studies on CGRP-(receptor) mAbs demonstrated excellent efficacy and tolerability in patients with chronic and episodic migraine including subjects with multiple unsuccessful conventional therapy attempts. However, more comparator trials showing superiority of mAbs versus oral preventatives, such as the HER-MEs study are needed. In summary, with the CGRP antibodies, a group of drugs has entered the market which will most likely not only significantly improve the quality of life of many individual migraine patients but could also reduce indirect health-care costs associated with migraine by reducing recurrent medical consultations.